KEBIJAKAN SISTEM PENDIDIKAN ISLAM MULTIDISIPLINER - Shelvia Loviana; Rima Kasturi; Nirva Diana; Eti Hadiati; Meriyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of a multidisciplinary Islamic education system policy in Indonesia and the role of Islamic educational leadership in supporting its success. The background of this research is based on the dichotomy between religious and general knowledge, which has long been a fundamental problem in Islamic education. Through library research and policy analysis, this study finds that multidisciplinary Islamic education is a crucial strategy in addressing the challenges of the Industrial Revolution 4.0 and Society 5.0. Key findings indicate that the Ministry of Religious Affairs has implemented policy transformation through curriculum integration, madrasah digitalization, and religious moderation programs. However, obstacles remain in the form of cultural resistance, limited human resources, and gaps in access to technology. Adaptive, collaborative, and Islamic-value-based leadership are key to strengthening the multidisciplinary Islamic education system in the future.